Perilaku Inovatif sebagai Mediasi Dampak Etos Kerja dalam Meningkatkan Kinerja Pelaku Usaha di Kabupaten Minahasa Selatan pada Era Resesi Ekonomi Global: Innovative Behavior as a Mediating Impact of Work Ethic in Improving the Performance of Business Actors in South Minahasa Regency in the Era of Global Economic Recession - Irvan Trang; Lucky Otto Herman Dotulong (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2023)
Human resources are an essential and vital asset in an organization. An organization cannot function without human resources. Facing the continuous development of the times and the increasingly evident technological disruption, business competition and competition for human resources are becoming more intense, including for business actors. They are required to have a high work ethic, be adaptable, responsive to innovation, exhibit innovative behavior, and be open to technological changes. Business actors must also be aware of fundamental changes in generating new ideas and value. To achieve this, business actors need a high work ethic through innovative behavior to improve their performance in maintaining and developing their businesses. This phenomenon is relevant in the current era of global economic recession, where many business actors are experiencing bankruptcy, closure, or insolvency, including in various regions. This study aims to analyze and develop variables and instruments that can identify indicators influencing the performance improvement of business actors in the current global recession era. The research method includes observation, population identification, sample determination (business actor respondents), surveys, questionnaire distribution, and data collection through closed and open-ended questions to obtain accurate results. The data obtained are then processed and evaluated for seminars and publication. The results of the study indicate that a high work ethic has a positive and significant direct effect on the innovative behavior of business actors, a high work ethic positively and significantly affects business performance, innovative behavior positively and significantly affects business performance, and a high work ethic affects business performance mediated by innovative behavior. This research is expected to contribute positively to all stakeholders (academics, businesspeople, government) in enhancing competitiveness and business sustainability amid the challenges of the global economic recession.